Evaluating Novel Threats to the Homeland Unmanned Aerial Vehicles and Cruise Missiles - Jackson, Brian A. (RAND Corporation, 2008)
Changes in technology and adversary behavior will invariably produce new threats that must be assessed by defense and homeland security planners. An example of such a novel threat is the use of cruise missiles or unmanned aerial vehicles (UAVs) by terrorist groups. Individual threats cannot be assessed in isolation, however, since adversaries always have many options for staging attacks. To examine this threat, RAND utilized a ?red analysis of alternatives? approach, wherein the benefits, costs, and risks of different options are considered from the point of view of a potential adversary. For several types of attacks, the suitability of these systems was compared against other options. This approach can help defense planners understand how the capabilities that different attack modes provide address key adversary operational problems. Given the insights this analysis produced about when these systems would likely be preferred by an attacker, RAND explored defensive options to address the threat. UAVs and cruise missiles represent a ?niche threat? within a larger threat context; therefore, defenses were sought that provide common protection against both this and other asymmetric threats. The monograph concludes with a discussion of cross-cutting lessons about this threat and the assessment of novel threats in general.